Product portfolio planning with customer-engineering interaction - Zhang, Yiyang (2008)
A critical decision facing many companies across many industries is the selection of an optimal mix of product attributes to offer in the marketplace, which is referred to as product portfolio planning. Product portfolio planning generally involves two stages, namely portfolio identification and optimization. The former aims to capture and understand customer needs effectively and accordingly to transform them into specifications of product offerings. The latter concerns how to determine an optimal mix of these identified offerings to offer in the marketplace.